THE DILEMMA OF THE CONCEPT OF CRIMINALITY - Sakalauskas, Gintautas (Socialinė teorija, empirija, politika ir praktika, 2009)
The article discusses the dilemma of the concept of criminality and it’s different reflections in Western and Soviet ideology. It is noted that the difference in these reflections still affects the understanding of the concept in countries with different historical background. Moreover, it heavily affects the understanding of criminality as phenomena as well as ideology of the crime prevention and control. Soviet tradition is characterized by an attempt to define criminality as precise as possible and to outline all its features. Soviet tradition has formed the concept that criminality is objective phenomena that causes a permanent threat to society that is why it shall be permanently “fought”. Western tradition pays much less attention to the definition of the concept, it limits itself by presentation of various theories of criminology as well as description of manifestations of criminal activity. Criminality can be compared to fashion, i.e. the phenomena that has no precise meaning, it comes from nowhere and it disappears into nowhere. However, it exists. Moreover, in a time of different crises it is fashionable to write and speak about the criminality without taking into consideration of concept’s ambiguity.